Emotion regulation in action: Use, selection, and success of emotion regulation in adolescents' daily lives. (January 2019) - Lennarz, Hannah K.; Hollenstein, Tom; Lichtwarck-Aschoff, Anna; Kuntsche, Emmanuel; Granic, Isabela
Successful emotion regulation (ER) is a central aspect of psychosocial functioning and mental health and is thought to improve and be refined in adolescence. Past research on ER has mainly focused on one-time measurements of habitual ER. Linking regulatory strategies to emotions in daily lives is key to understanding adolescents' emotional lives. Using an Experience Sampling Method with 78 adolescents ( M age = 13.91, SDage = .95, 66% girls), we investigated the use, selection, and success in down-regulating negative emotions of eight ER strategies across 44 assessments. Acceptance was the strategy employed most often followed by problem-solving, rumination, distraction, avoidance, reappraisal, social support, and suppression. Interestingly, negativity of the event influenced the use of ER strategies: With low intensity negative emotions, acceptance was more likely to be used, and with high intensity negative emotions, suppression, problem-solving, distraction, avoidance, social support, and rumination were more likely to be used. With regard to success, multilevel models revealed that problem-solving, reappraisal, and acceptance were more successful in down-regulating negative emotions than rumination. Further, among girls, no relations between the momentary use of ER strategies and depressive symptoms was found. Among boys, a negative relation between acceptance and depressive symptoms emerged. Results from this study suggest that there is a reciprocal relationship between the intensity of negative emotions and ER strategies and that gender differences may exist. Taken together, this study showed which ER strategies are used by a healthy adolescent sample, and these results are discussed with regard to their theoretical and practical importance.